TANGGUNG JAWAB PENGANGKUT DALAM PENGIRIMAN PAKET BARANG DAN HEWAN OLEH PT. HERONA EXPRESS - Gita Puspitasari Marganingtyas, Rinitami Njatrijani *), Paramita Prananingtyas (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Transportation has a very important role in the life of the community to facilitate the flow of goods and people traffic. Transportation in Indonesia increases its speed according to the physical or psychological development. PT. Herona Express is one company that is enganged in the transportation of goods and animals by rail transport. Inpractice PT. Herona Express have responbilities during the process of transporting it lats. Based on this, the authors conducted a study regarding the responbility of PT. Herona Express as a provider of freight. The method used in this study is empirical juridical method by examining secondary data first and the followed by examining the primary data in the field. The primary data obtained from interview by the carrier and secondary data obtained from the study of literature in the form of legislation or other sources related to the study. The data obtained was analyzed using qualitative analysis. The results of these studies indicate that the responsibility PT. Herona Express begins when the goods are in their control, during the shipping process take place until such time as the deposit to the recipient. PT. Herona Express responsible for delivering the goods and animals safely and be responsible for losses incurred due to damage and loss of goods and animals during the process of transporting it lasts. Completion of the problems occurred due to delay in delivery of goods and animals caused by natural disasters resolved by the parties through kinship or win-win solution. The conclusion of this research is the implementation of the transport will run well when both parties, both the shipper and the carrier can be fully aware of their rights and responsibilities and are equally comply with existing regulations on the transport.